The Expression of Genes Encoding Secreted Proteins in Medicago truncatula A17 Inoculated Roots - LUCIA KUSUMAWATI; KATHRYN KURAN; NIJAT IMIN; ULRIKE MATHESIUS; MICHAEL DJORDJEVIC (HAYATI Journal of Biosciences, 2013)
Subtilisin-like serine protease (MtSBT), serine carboxypeptidase (MtSCP), MtN5, non-specific lipid transfer protein (MtnsLTP), early nodulin2-like protein (MtENOD2-like), FAD-binding domain containing protein (MtFAD-BP1), and rhicadhesin receptor protein (MtRHRE1) were among 34 proteins found in the supernatant of M. truncatula 2HA and sickle cell suspension cultures. This study investigated the expression of genes encoding those proteins in roots and developing nodules. Two methods were used: quantitative real time RT-PCR and gene expression analysis (with promoter:GUS fusion) in roots. Those proteins are predicted as secreted proteins which is indirectly supported by the findings that promoter:GUS fusions of six of the seven genes encoding secreted proteins were strongly expressed in the vascular bundle of transgenic hairy roots. All six genes have expressed in 14-day old nodule. The expression levels of the selected seven genes were quantified in Sinorhizobium-inoculated and control plants using quantitative real time RT-PCR. In conclusion, among seven genes encoding secreted proteins analyzed, the expression level of only one gene, MtN5, was up-regulated significantly in inoculated root segments compared to controls. The expression of MtSBT1, MtSCP1, MtnsLTP, MtFAD-BP1, MtRHRE1 and MtN5 were higher in root tip than in other tissues examined.